The influence of self leadership on creative self efficacy and innovative work behavior - Supriyani, Tari; Azizah, Siti Nur (Institute of Computer Science (IOCS), 2024)
This research aims to determine the influence of self-leadership, creative self-efficacy, and innovative work behavior of Driving Teachers in Gombong District. The sample population is driving teachers in Gombong District. Questionnaires were distributed by distributing questionnaires directly to driving teachers. SPSS version 22 software was used to model the relationships between the variables studied. The research results confirm the existence of a relationship between self-leadership and creative self-efficacy and innovative work behavior. Creative self-efficacy influences innovative work behavior. The research results show that there is a significant mediating effect of creative self-efficacy on the relationship between self-leadership and innovative work behavior. Based on the model presented in this research, we can conclude that self-leadership has an impact on creative self-efficacy and innovative work behavior